Aerobic capacity and respiratory indices of junior cross-country skiers and biathletes during incremental exercise testing - Tortu, E.; Ouergui, I.; Deliceoglu, G.; Keles, A.; Ulupinar, S.; Özbay, S.; Gençoglu, C.; Ardigò, L. P. (Scientific Reports, 2024)
The present study compared the isocapnic buffering phase (ICB), hypocapnic hyperventilation phase, ventilatory threshold (VT), respiratory compensation point (RCP), and maximum oxygen uptake (VO2max) among biathlon and cross-country ski athletes during an incremental exercise test. 37 male and 33 female Turkish National Team athletes volunteered to participate in the research. Body fat percentage, lean mass, and fat mass values of athletes were measured using the bioelectrical impedance analysis method, and oxygen consumption (VO2) was measured with a portable cardiopulmonary exercise test system with a ramp protocol on the treadmill. In VT, RCP, and VO2max phases, male athletes had higher VO2 and speed values than female athletes (p < 0.05). In contrast, they had similar values across different categories of sports (biathlon and cross-country skiing) (p > 0.05). Additionally, XC skiers and males had higher absolute (Abs) VO2 and mass-normalized (Rel) VO2 values than biathletes and females in exhaustion times and ICBs (p < 0.05). In contrast, they had similar Abs VO2 and Rel VO2 values in hypocapnic hyperventilation phases (p > 0.05). In addition, XC skiers and males had higher absolute (Abs) VO2 and relative (Rel) VO2 values than biathletes and females in exhaustion times and ICBs (p < 0.05). In contrast, they had similar Abs VO2 and Rel VO2 values in hypocapnic hyperventilation phases (p > 0.05). These results indicate significant differences in physiological profiles between male and female athletes and between XC skiers and biathletes.